Researcher Profile: An Interview with Jorge Ruiz-Menjivar - Jorge Ruiz-Menjivar (Journal of Financial Therapy, 2016)
Jorge Ruiz-Menjivar is originally from San Salvador, El Salvador, but has had the privilege to live in several Latin American countries (e.g., Nicaragua, Costa Rica, among others), and to travel through many other regions in the world. He obtained a Bachelor’s degree in Accounting at the University of New Orleans-Louisiana State University. Then, he went on to earn a Master’s degree in Personal and Family Financial Planning at the University of Florida under the supervision of Drs. Michael S. Gutter and Martie Gillen. Recently, Jorge finished his Doctoral degree in Financial Planning, Housing and Consumer Economics from the University of Georgia under the supervision of Drs. John E. Grable and George Engelhard, Jr.
Keywords: financial therapy research; financial therapy